2018
DOI: 10.1016/j.bbrc.2018.07.149
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide attenuates oxidative stress in fetal human lung endothelial cells via superoxide dismutase 2 and catalase

Abstract: Hyperoxia-induced oxidative stress contributes to the pathogenesis of bronchopulmonary dysplasia (BPD), the most common respiratory morbidity of preterm infants. Importantly, the disease lack specific therapies and is associated with long-term cardio-pulmonary and neurodevelopmental morbidities, signifying the need to discover novel therapies and decrease the disease burden. We and others have demonstrated that leflunomide, a food and drug administration approved drug to treat humans with rheumatoid arthritis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, there were no symptoms of oxidative stress in teriflunomide treated cells. Despite this fact, there have been several reports of oxidative stress reduction—e.g., in fetal human pulmonary arterial endothelial cells due teriflunomide treatment [ 34 ]—and its ability to preserve peripheral nerve mitochondria from oxidative stress [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no symptoms of oxidative stress in teriflunomide treated cells. Despite this fact, there have been several reports of oxidative stress reduction—e.g., in fetal human pulmonary arterial endothelial cells due teriflunomide treatment [ 34 ]—and its ability to preserve peripheral nerve mitochondria from oxidative stress [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress response: More and more population studies have shown that oxidative stress plays an important role in the pathogenesis of asthma, and the oxidative stress level is mainly refl ected in the levels of various antioxidant enzymes [23][24][25]. I-Jen W, et al [20] found that individuals with Superoxide Dismutase 2 (SOD2) (rs5746136) TT genotype had higher risk of asthma and higher level of MEHHP in vivo than those with CC genotype.…”
Section: Potential Mechanisms Of Childhood Asthma Induced By Early Life Exposure To Paesmentioning
confidence: 99%